Pengaruh Kualitas Produk dan Persepsi Risiko terhadap Keputusan Pembelian Sunscreen Emina di Kalangan Remaja - Utami Puji Lestari; Masrifah Masrifah; Dewi Sekar Arum (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to evaluate the impact of product quality and risk perception on consumer decisions in purchasing Emina brand sunscreen using a survey method on 100 product user respondents. The findings of the study indicate that product quality and risk perception contribute significantly to purchasing decision making. These findings underline the importance of product quality aspects in shaping consumer preferences, while revealing the unique role of risk perception that can actually drive purchasing interest when supported by adequate information. This study provides insight into the importance of product quality management and effective communication strategies in reducing consumer doubts to improve purchasing decisions for skincare products, especially Emina sunscreen.